A sizing solution for a fiber skeleton material

CN117779473BActive Publication Date: 2026-10-27HAILIDE NEW MATERIAL RES (SHANGHAI) CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211156724.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-22
Publication Date
2026-10-27
Estimated Expiration
2042-09-22

AI Technical Summary

Technical Problem

较为主流的有以下几种:(1)将环氧或异氰酸酯组分混合进RFL,该种方法反应选择性较低,环氧和异氰酸酯的利用率不高;(2)添加氯苯酚类物质,该方法利用氯苯酚对帘线的溶胀作用,使得界面发生渗透扩散,增强浸胶和帘线的作用力,但该方法使用的原料含卤素,未来受环保标准提高的制约较大;(3)添加含氮化合物,主要是氨基苯酚,该法主要利用的是氨基对帘线酯键的氨解作用,对帘线有一定的损伤,且有文献报道此类配方稳定性不佳,不宜储存、生产;(4)使用非RF体系的浸胶,目前主要受制于成本和浸胶与橡胶配方的兼容性,尚未大规模推广使用

Benefits of technology

[0039]本申请浸胶液中的含硫活性化合物能够通过环氧开环反应或硅氧烷取代反应与酚醛粘合树脂发生化学键合,同时通过硫键与橡胶和胶乳发生化学键合。因此,本申请能够提高浸胶与橡胶之间的作用强度,使得浸胶配方中可以减少非极性胶乳的添加量,增加极性酚醛粘合树脂的添加量,增强浸胶与聚酯的作用强度,最终达到提高整体粘合力的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0003859092040000031
    Figure BDA0003859092040000031
Patent Text Reader

Abstract

The application discloses a sizing liquid for fiber skeleton material, which comprises: a one-bath sizing liquid suitable for one-bath impregnation method or a second sizing liquid suitable for two-bath impregnation method; the solid content of the one-bath sizing liquid is 10-45%, and the dry weight of the one-bath sizing liquid comprises 15-70% of phenolic adhesive resin, 20-70% of latex and 3-20% of sulfur-containing active compound; the solid content of the second sizing liquid is 10-45%, and the dry weight of the second sizing liquid comprises 10-60% of phenolic adhesive resin, 30-90% of latex and 3-20% of sulfur-containing active compound. The application can improve the action strength between the sizing and rubber, so that the adding amount of non-polar latex in the sizing liquid formula can be reduced, the adding amount of polar phenolic adhesive resin can be increased, the action strength between the sizing and polyester can be enhanced, and finally the effect of improving the overall adhesion is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of impregnation solution technology, specifically relating to an impregnation solution for a fiber skeleton material. Background Technology

[0002] In rubber products, fiber-reinforced reinforcing materials primarily function to bear loads and maintain dimensional stability. Their adhesion to rubber plays a decisive role in the performance and lifespan of the rubber products. Common applications include conveyor belts, tires, and hoses. Commonly used reinforcing materials include metals, cellulose, nylon, and polyester.

[0003] For polyester backbone materials, due to the significant differences in polarity and rigidity between polyester fibers and the rubber matrix, an impregnation process is required to create an impregnated layer to improve the interfacial adhesion between the two phases. Current mainstream impregnation systems are mostly RFL (resorcinol-formaldehyde) systems, where R is resorcinol, F is formaldehyde, and L is latex. This is a composite impregnation emulsion formed by the condensation polymerization of resorcinol and formaldehyde to form a phenolic resin, with the latex encapsulated within. This RFL system primarily bonds to the fibers through intermolecular forces of RF and crosslinks with the rubber through co-vulcanization of the latex. For nylon containing a large number of amide bonds, only a small amount of RF is needed to generate a large number of intermolecular forces, such as hydrogen bonds; therefore, single-bath RFL can achieve satisfactory bonding results. However, for polyester materials such as polyethylene terephthalate (PET), the lack of surface groups capable of generating intermolecular forces such as hydrogen bonds makes it difficult to achieve satisfactory bonding results. In industrial applications, a two-bath impregnation method is generally used, where epoxy-isocyanate is used as the first bath, followed by RFL as the second bath. While the two-bath method achieves satisfactory adhesion, it requires two impregnation and drying processes, resulting in significant energy consumption.

[0004] For polyester fiber skeleton materials, existing technologies have also attempted one-bath impregnation. The more mainstream methods are as follows: (1) Mixing epoxy or isocyanate components into RFL. This method has low reaction selectivity and low utilization of epoxy and isocyanate; (2) Adding chlorophenols. This method utilizes the swelling effect of chlorophenols on the cord to cause interfacial penetration and diffusion, enhancing the interaction between the impregnation and the cord. However, the raw materials used in this method contain halogens, which will be greatly restricted by the future increase in environmental standards; (3) Adding nitrogen-containing compounds, mainly aminophenols. This method mainly utilizes the ammonolysis of the ester bonds of the cord by amino groups, which can cause some damage to the cord. Moreover, literature reports that such formulations have poor stability and are not suitable for storage and production; (4) Using non-RF system impregnation. Currently, this method is mainly limited by cost and compatibility between impregnation and rubber formulations and has not been widely promoted. In addition, the impregnation formulations in the above-mentioned existing technologies often have the problem of focusing on the adhesion of polyester / rubber while the adhesion to the other interface is poor. Their overall performance is somewhat inferior to that of two-bath impregnation.

[0005] Therefore, how to achieve good product performance in the formulation and production of resin impregnation, especially in the one-bath impregnation process, while taking into account environmental protection and cost reduction, is a technical problem that urgently needs to be solved. Summary of the Invention

[0006] In view of the shortcomings or deficiencies of the prior art, the technical problem to be solved by this application is to provide an impregnation solution for a fiber skeleton material.

[0007] To solve the above-mentioned technical problems, this application provides the following technical solution:

[0008] This application discloses an impregnation solution for a fiber skeleton material, comprising: a one-bath impregnation solution suitable for a one-bath impregnation method or a second impregnation solution suitable for a two-bath impregnation method; the one-bath impregnation solution has a solid content of 10% to 45%, and its dry weight comprises: 15% to 70% phenolic adhesive resin, 20% to 70% latex, and 3% to 20% sulfur-containing active compounds; the second impregnation solution has a solid content of 10% to 45%, and its dry weight comprises: 10% to 60% phenolic adhesive resin, 30% to 90% latex, and 3% to 20% sulfur-containing active compounds.

[0009] Furthermore, the solid content of the one-bath impregnation solution is 15% to 35%, and its dry weight includes: 30% to 70% phenolic adhesive resin, 20% to 60% latex, and 5% to 15% sulfur-containing active compounds.

[0010] Furthermore, the second impregnation solution has a solid content of 15% to 35%, and its dry weight includes: 20% to 50% phenolic adhesive resin, 50% to 80% latex, and 5% to 15% sulfur-containing active compounds.

[0011] Furthermore, the one-bath impregnation solution and / or the second impregnation solution further include: additives with a total proportion of less than or equal to 10%; the additives include: pH adjusters, surfactants, film-forming agents, antioxidants and / or crosslinking catalysts.

[0012] Furthermore, the sulfur-containing active compound includes: a first compound and / or a second compound;

[0013] The general structural formula of the first compound is as follows:

[0014]

[0015] In the above formula, m is a positive integer, and the sum of n and k is greater than or equal to 1;

[0016] The general structural formula of the second compound is as follows:

[0017]

[0018] In the above formula, X is a hydrogen atom, or R1, or -R1-Si(R2) )b (OR3) a The sum of a and b is 3, and c is a positive integer.

[0019] Furthermore, m is preferably 1 to 2.

[0020] Furthermore, n is preferably 1 to 4.

[0021] Furthermore, n is preferably 1 to 2.

[0022] Furthermore, k is preferably 1 to 4.

[0023] Furthermore, k is preferably 1 to 2.

[0024] Furthermore, c is preferably 1 to 3.

[0025] Furthermore, c is preferably 1.

[0026] Furthermore, 'a' is preferably 3.

[0027] Further, R, R', and R1 each comprise: an unsubstituted or branched alkyl chain, or an unsubstituted or branched alkenyl chain, or an unsubstituted or branched alkynyl chain, or an unsubstituted or branched heterochain, or an unsubstituted or branched cycloalkyl chain, or an unsubstituted or branched cyclic heterochain, or an unsubstituted or branched cyclic chain containing double bonds, or an unsubstituted or branched cyclic chain containing triple bonds. Alternatively, unsubstituted or branched benzene, or unsubstituted or branched fused ring, or unsubstituted or branched heterocycle; the heterochain is a carbon chain containing oxygen atoms, a carbon chain containing nitrogen atoms, and / or a carbon chain containing sulfur atoms; the heterocycle includes: pyridine, thiophene, or furan; the branch includes: alkyl chain, alkenyl chain, alkynyl chain, heterochain, cycloalkyl chain, cyclic heterochain, cyclic chain containing double bonds, cyclic chain containing triple bonds, benzene, fused ring, and / or heterocycle.

[0028] Furthermore, R, R', and R1 each include: -(CH2) e -O(CH2CH2O) d -(CH2) e -, d is 1~4, e is 1~2; or, C1~C 10 Carbon chain; or, aromatic nucleus structure with 1 to 2 aromatic rings.

[0029] Furthermore, when n is zero, R also includes: independent hydrogen atoms; when k is zero, R' also includes: independent hydrogen atoms.

[0030] Furthermore, the alkyl chain, the alkenyl chain, the alkynyl chain, the heterochain, the cycloalkyl chain, the cyclic heterochain, the cyclic double-bonded chain, the cyclic triple-bonded chain, the benzene, the fused ring, and the heterochain have substituents, the substituents including: hydroxyl, carboxyl, alkoxy, amino, halogen, ester, and / or amide groups.

[0031] Furthermore, R has 6 or fewer carbon atoms.

[0032] Furthermore, when the number of carbon atoms in R is greater than or equal to 5, the mass fraction of heteroatoms is greater than or equal to 15% to ensure the hydrophilicity of R.

[0033] Furthermore, R1 is CH2-CH2-CH2.

[0034] Furthermore, R2 and R3 each comprise: C1 to C2 alkyl groups, and R2 or R3 has R4 substitution; said R4 comprises: hydroxyl, carboxyl, carboxylate, sulfonic acid, sulfonate, thiosulfate, thiosulfate and / or amino.

[0035] Further, the latex includes: styrene-butadiene latex, styrene-butadiene-pyridine latex, butyl pyridine latex, vinylpyridine latex, nitrile latex, hydrogenated nitrile latex, polybutadiene latex, chloroprene latex and / or natural latex.

[0036] Further, the styrene-butadiene latex comprises: styrene-butadiene latex end-capped with carboxyl groups, hydroxyl groups, acid anhydride, and / or grafted modified; the styrene-butadiene pyridine latex comprises: styrene-butadiene pyridine latex end-capped with carboxyl groups, hydroxyl groups, acid anhydride, and / or grafted modified; the nitrile butadiene latex comprises: nitrile butadiene pyridine latex end-capped with carboxyl groups, hydroxyl groups, acid anhydride, and / or grafted modified; the vinylpyridine latex comprises: vinylpyridine latex end-capped with carboxyl groups, hydroxyl groups, acid anhydride, and / or grafted modified; the nitrile butadiene latex comprises: nitrile butadiene pyridine latex end-capped with carboxyl groups, hydroxyl groups, acid anhydride, and / or grafted modified; The hydrogenated nitrile butadiene latex comprises: carboxyl, hydroxyl, anhydride-terminated and / or graft-modified hydrogenated nitrile butadiene latex; the polybutadiene latex comprises: carboxyl, hydroxyl, anhydride-terminated and / or graft-modified polybutadiene latex; the chloroprene latex comprises: carboxyl, hydroxyl, anhydride-terminated and / or graft-modified chloroprene latex; the natural latex comprises: carboxyl, hydroxyl, anhydride-terminated and / or graft-modified natural latex.

[0037] Furthermore, the phenolic adhesive resin is formed by the condensation polymerization of phenolic monomers and aldehyde monomers; the phenolic monomers include: resorcinol, phloroglucinol, phenol, chlorophenol, aminophenol, or alkylphenol; the aldehyde monomers include: formaldehyde, alkyl aldehyde, benzaldehyde, benzoxaldehyde, or furfural.

[0038] Compared with the prior art, this application has the following technical effects:

[0039] The sulfur-containing active compounds in the impregnation solution of this application can chemically bond with phenolic adhesive resin through epoxy ring-opening reaction or siloxane substitution reaction, and simultaneously chemically bond with rubber and latex through sulfur bonds. Therefore, this application can improve the interaction strength between the impregnation solution and the rubber, allowing for a reduction in the amount of non-polar latex added and an increase in the amount of polar phenolic adhesive resin added to the impregnation formulation, thereby enhancing the interaction strength between the impregnation solution and the polyester, ultimately achieving the effect of improving overall adhesion.

[0040] The methods for synthesizing sulfur-containing active compounds in this application are diverse and simple, and their structures are easy to adjust. The molecular structure can be adjusted according to product requirements, which is conducive to further performance improvement and application expansion.

[0041] This application enhances the affinity between the impregnation layer and the rubber layer in the one-bath impregnation method, avoids the large energy consumption caused by the two-bath impregnation process, effectively improves production efficiency, enhances adhesion, and reduces production costs. Of course, this application can also be used in the second impregnation stage of the two-bath impregnation method.

[0042] Compared to other one-bath impregnation formulations, this application avoids damage to the cords and the addition of more toxic and harmful substances, and can generate chemical cross-linking between the impregnating agent and the rubber during the impregnation process to achieve reliable adhesion.

[0043] This application has good compatibility with traditional impregnation solutions in terms of equipment and processes. Detailed Implementation

[0044] The following embodiments further illustrate this application, but the implementation and protection of this application are not limited thereto. It should be noted that any processes not specifically described below are methods that can be implemented or understood by those skilled in the art by referring to existing technology. Reagents or instruments whose manufacturers are not specified are considered to be conventional products that can be purchased commercially.

[0045] The reagents used in the following examples:

[0046] Acidic resorcinol-formaldehyde precondensation resin: self-made;

[0047] Resorcinol: Analytical grade (AR), 99%, Adamas;

[0048] Formaldehyde: AR, 37%, Chinese medicine;

[0049] Ammonia water: AR, 25-28%, Chinese medicine;

[0050] Deionized water: homemade;

[0051] Ethyl acetate: distillation grade, Adamas;

[0052] Nano sulfur dispersion: 10%, Shanghai Huzheng;

[0053] Sodium sulfide nonahydrate: AR, 98%, general reagent (GReagent');

[0054] Methanol: Sinopharm, AR, 99%;

[0055] Butadiene-pyridine latex (VP): Commercially available, 40%;

[0056] Styrene-butadiene rubber latex (SBR): Commercially available, 40%;

[0057] Natural latex (NR): Commercially available, 40%;

[0058] m-chloroperoxybenzoic acid (mCPBA), Adamas;

[0059] Sulfoxide dichloride: AR, 98%, Adamas;

[0060] N,N-Dimethylformamide (DMF): AR, 99%, Adamas;

[0061] Ethylene glycol: Industrial grade, with a purity of 99.5% as determined by quality inspection, and a water content of 0.04% as determined by the Karl Fischer method;

[0062] Sulfuric acid: AR, 98%;

[0063] Lactic acid: AR, 90%, after being dehydrated by distillation and then dried in two steps with anhydrous sodium sulfate and 3A molecular sieve;

[0064] Ether-chain epoxy precursor: self-made, specifically starting from 2-allyl hydroxyethyl ether, through two reaction steps of thionyl chloride chlorination and epoxidation, to obtain the precursor 2-epoxy-2'-chloroethyl ether, the structure of which is shown below:

[0065]

[0066] Aromatic epoxy precursor: self-made, specifically obtained by epoxidation of p-chloromethylstyrene with mCPBA, as shown below:

[0067]

[0068] JH-S69 - Industrial grade, manufactured by Hubei Jianghan Organosilicon, structure is shown below:

[0069]

[0070] JH-S75 - Industrial Grade, manufactured by Hubei Jianghan Organosilicon, structure is shown below:

[0071]

[0072] This application discloses an impregnation solution for a fiber skeleton material, comprising: a one-bath impregnation solution suitable for a one-bath impregnation method or a second impregnation solution suitable for a two-bath impregnation method; the one-bath impregnation solution has a solid content of 10% to 45%, and its dry weight comprises: 15% to 70% phenolic adhesive resin, 20% to 70% latex, and 3% to 20% sulfur-containing active compounds; the second impregnation solution has a solid content of 10% to 45%, and its dry weight comprises: 10% to 60% phenolic adhesive resin, 30% to 90% latex, and 3% to 20% sulfur-containing active compounds.

[0073] When the solid content is less than 10%, the dipping solution contains more water than glue, resulting in poor adhesion; when the solid content is more than 45%, the dipping solution has poor stability and high viscosity, making operation difficult.

[0074] Preferably, the solid content is 20% to 30%.

[0075] The impregnation solution for the fiber skeleton material proposed in this application can improve the interaction strength between the impregnating resin and the rubber, allowing for a reduction in the amount of non-polar latex and an increase in the amount of polar phenolic adhesive resin in the impregnation solution formulation. This enhances the interaction strength between the impregnating resin and the polyester, ultimately improving the overall adhesive strength. Specific embodiments are provided below for illustration.

[0076] Example 1

[0077] The sulfur-containing active compound has the following chemical structure, namely compound A:

[0078]

[0079] The specific preparation process of compound A is as follows:

[0080] Take 240g of sodium sulfide nonahydrate, add 320g of 10% nano sulfur solution, and stir at room temperature under nitrogen protection until the solution becomes clear to obtain sodium sulfide solution.

[0081] The sodium persulfide solution has a mass fraction of approximately 20%.

[0082] Take 150g of epichlorohydrin into a 500ml round-bottom flask, cool it to 5℃ in an ice-water bath, and add 50g of 20% sodium persulfate solution dropwise. After the addition is complete, continue stirring in the ice-water bath for 2 hours until the orange-yellow color of sodium persulfate completely disappears.

[0083] The reaction mixture was diluted with 100 mL of saturated brine and extracted with 200 mL of ethyl acetate. After separation, the organic phase was retained. The mixture was washed with saturated brine until the pH did not exceed 9, yielding a golden-yellow organic phase. The organic phase was then removed by solvent removal using a rotary evaporator, followed by distillation under high vacuum using an oil pump to remove residual epichlorohydrin, yielding the product. The product was a golden-yellow viscous liquid, and its structure and purity were confirmed by peak area normalization (GC-MS). Specifically, the yield was 13.1 g, with a purity of approximately 92% and a yield of 89%.

[0084] Example 2

[0085] The sulfur-containing active compound has the following chemical structure, namely compound B:

[0086]

[0087] The specific preparation process of compound B is as follows:

[0088] 200 g of the ether-chain epoxy precursor compound was placed in a 1000 ml round-bottom flask and cooled to 5 °C in an ice-water bath. 50 g of the 20% sodium persulfide solution described in Example 1 was added dropwise over 3 hours. The reaction mixture was stirred in the ice-water bath for another 2 hours until the orange-yellow color of the sodium persulfide essentially disappeared. After the reaction was complete, the reaction mixture was diluted with saturated brine and extracted with ethyl acetate. The extracted organic phase was washed with saturated brine until the pH was no higher than 9, yielding a golden-yellow organic phase. After removing the solvent from this organic phase using a rotary evaporator, it was distilled under high vacuum using an oil pump to remove the residual ether-chain epoxy precursor compound, yielding the product. The product was a golden-yellow viscous liquid, and its structure and purity were confirmed by GC-MS. Specifically, the yield was 17.9 g, with a purity of approximately 85% and a yield of 71%.

[0089] Example 3

[0090] The sulfur-containing active compound has the following chemical structure, namely compound C:

[0091]

[0092] The specific preparation process of compound C is as follows:

[0093] 200 g of the aromatic epoxy precursor compound was placed in a 1000 ml round-bottom flask and cooled to 5 °C in an ice-water bath. 50 g of the 20% sodium persulfide solution described in Example 1 was added dropwise over 3 hours. The reaction mixture was stirred in the ice-water bath for another 3 hours until the orange-yellow color essentially disappeared. After the reaction was complete, the reaction mixture was diluted with saturated brine and extracted twice with ethyl acetate. The extracted organic phase was washed with saturated brine until the pH was no higher than 9, yielding a yellow organic phase. The organic phase was then subjected to a high vacuum distillation using an oil pump to remove residual aromatic epoxy precursor compounds, yielding the product. The product was a golden-yellow viscous liquid, and its structure and purity were confirmed by GC-MS. Specifically, the yield was 27 g, with a purity of approximately 81% and a yield of 76%.

[0094] Example 4

[0095] The sulfur-containing active compound has the following chemical structure, namely compound D:

[0096]

[0097] The specific preparation process of compound D is as follows:

[0098] 48g of JH-S75 coupling agent, 62g of ethylene glycol, and 100mg of concentrated sulfuric acid were placed in a 250ml round-bottom flask, which was connected to a vacuum distillation apparatus. At room temperature, the ethylene glycol and silane coupling agent separated into two layers, and after thorough stirring, a turbid emulsion was obtained. The reaction mixture was heated to 80°C, and a circulating water vacuum pump was used to reduce the pressure. At this point, the reaction mixture began to boil, and liquid condensed in the distillation condenser. As the reaction proceeded, the liquid phase gradually became clear and transparent, and then the viscosity increased. This colorless, clear, viscous liquid is compound D. 2g of compound D was dispersed in 50ml of deionized water, and the product was found to be a homogeneous emulsion that remained stable after stirring was stopped. The product was characterized by 1H NMR spectroscopy, revealing that the residual ethoxy groups were 0.81 per silicon atom.

[0099] Example 5

[0100] The sulfur-containing active compound has the following chemical structure, namely compound E:

[0101]

[0102] The specific preparation process of compound E is as follows:

[0103] 54g of JH-S69 coupling agent, 62g of ethylene glycol, and 100mg of concentrated sulfuric acid were placed in a 250ml round-bottom flask, which was connected to a vacuum distillation apparatus. At room temperature, the ethylene glycol and silane coupling agent separated into two layers, and after thorough stirring, a turbid emulsion was obtained. The reaction mixture was heated to 80°C, and a circulating water vacuum pump was used to reduce the pressure. At this point, more boiling occurred in the reaction mixture, and liquid condensed and precipitated in the distillation condenser. As the reaction proceeded, the liquid phase gradually became basically clear and transparent, and then the viscosity increased. This light yellow, clear, viscous liquid is compound E. 2g of compound E was dispersed in 50ml of deionized water, and the product was found to be a homogeneous emulsion that remained stable after stirring was stopped. The product was characterized by 1H NMR spectroscopy, revealing that the residual ethoxy groups were 0.95 per silicon atom.

[0104] Example 6

[0105] The sulfur-containing active compound has the following chemical structure, namely compound F:

[0106]

[0107] The specific preparation process of compound F is as follows:

[0108] 200g of 90% lactic acid was distilled to remove approximately 12g of water and then dissolved in 400g of anhydrous ethanol to prepare a solution. After drying using a 3A molecular sieve and sodium sulfate, the ethanol was removed by rotary evaporation to obtain dry lactic acid. 60g of the dried lactic acid was mixed with 48g of JH-S75 coupling agent in a 250ml flask, heated to 60℃, and the ethanol was removed under vacuum. After reacting for 4 hours, the mixture was cooled to room temperature to obtain a white solid compound F. Compound F was characterized by 1H NMR spectroscopy, revealing a residual ethoxy group of 0.41 per silicon atom.

[0109] Example 7

[0110] The sulfur-containing active compound has the following chemical structure, namely compound G:

[0111]

[0112] The specific preparation process of compound G is as follows:

[0113] 200g of 90% lactic acid was dissolved in 400g of anhydrous ethanol to prepare a solution. After drying using a 3A molecular sieve and sodium sulfate, the ethanol was removed by rotary evaporation to obtain dry lactic acid. 19g of the dried lactic acid was mixed with 48g of JH-S75 coupling agent in a 125ml flask, heated to 60℃, and the ethanol was removed under vacuum. After reacting for 4 hours, the mixture was cooled to room temperature to obtain a white solid compound G. The product was characterized by 1H NMR spectroscopy, which revealed that it contained 2.0 residual ethoxy groups per silicon atom.

[0114] Example 8

[0115] The specific preparation process and addition amount of the impregnation solution in this embodiment are shown in Table 1.

[0116] Step 1: Preparation of Solution I. Dissolve 5g of resorcinol in 77g of water, then add 8g of formaldehyde, followed by 5g of ammonia. Stir at 25°C for 10 minutes, then slowly add 70g of butyl-butadiene rubber latex over the next 10 minutes, followed by slowly adding 35g of styrene-butadiene rubber latex over the next 5 minutes. The total mass of the mixture is 200g. The above product is then slowly stirred at room temperature and aged for 3 days to form Solution I.

[0117] Step 2: Preparation of Solution II. Add 80g of pre-condensed RF resin (50% aqueous solution) to 25g of ammonia and 86g of deionized water, and stir until homogeneous and stable to form a stable aqueous solution. Under rapid stirring, the solution exhibits a brown, homogeneous, and stable state, forming Solution II.

[0118] Step 3: Mixing the adhesive. After preparing solution II, immediately mix it with solution I, and then add 9g of the sulfur-containing active compound prepared in Example 1 to obtain the impregnation solution.

[0119] The impregnation test process in this embodiment:

[0120] The test cord used was 2000D / 2 polyester high-modulus, low-shrinkage cord manufactured by Hailide New Materials. The test was conducted on a single-wire impregnation testing machine under a tension of 4.0–5.0 N. The cord remained in the impregnation tank for approximately 8 seconds. The first oven temperature was 175℃, with a residence time of approximately 4 minutes; the second oven temperature was 240℃, with a residence time of approximately 4 minutes.

[0121] The impregnated cords obtained by the above method were subjected to CRA peel tests according to the test method of GB / T40725-2021. The total peel force of the five cords and the grade of rubber coating on the cord surface were recorded, denoted as grades A to E. The CRA peel force of the above impregnated cords was 125.19 N, and the amount of rubber adhering to the peel surface was judged to be grade A.

[0122] Example 9

[0123] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that the pre-condensed RF resin, which is the most abundant in this application, was added in this embodiment. The specific amount added is shown in Table 1. A uniform and stable latex was obtained. After testing, the CRA peel force of the impregnated cord was 116.07 N, and the amount of adhesive on the peel surface was judged to be Grade A.

[0124] Example 10

[0125] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that this embodiment added the minimum amount of pre-condensed RF resin of this application. The specific amount added is referred to Table 1. A uniform and stable latex was obtained. After testing, the CRA peel force of the impregnated cord was 87.45N, and the amount of adhesive on the peel surface was judged to be Grade B.

[0126] Example 11

[0127] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that the sulfur-containing active compound in the minimum amount of this application was added in this embodiment. The specific amount added is referred to Table 1. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 89.62N and the amount of adhesive on the peel surface was judged to be Grade B.

[0128] Example 12

[0129] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that the sulfur-containing active compound with the largest amount in this application was added in this embodiment. The specific amount added is referred to Table 1. A uniform and stable latex was obtained. After testing, the CRA peel force of the impregnated cord was 117.28N, and the amount of adhesive on the peel surface was judged to be Grade A.

[0130] Example 13

[0131] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that compound B was used to replace compound A in this embodiment. The specific amount added is referred to Table 1. A uniform and stable latex was obtained. After testing, the CRA peel force of the impregnated cord was 107.28 N, and the amount of adhesive on the peel surface was judged to be Grade A.

[0132] Example 14

[0133] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that compound C was used to replace compound A in this embodiment. The specific amount added is referred to Table 1. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 113.79 N after testing, and the amount of adhesive on the peel surface was judged to be Grade A.

[0134] Example 15

[0135] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that natural latex was used instead of styrene-butadiene latex in this embodiment. The specific amount added is referred to Table 2. A uniform and stable latex was obtained. After testing, the CRA peel force of the impregnated cord was 122.31N, and the amount of adhesive on the peel surface was judged to be Grade A.

[0136] Example 16

[0137] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that phenol was used instead of resorcinol in this embodiment. The specific amount added is referred to Table 2. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 106N after testing, and the amount of adhesive on the peel surface was judged to be Grade A.

[0138] Example 17

[0139] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that furfural was used to replace resorcinol in this embodiment. The specific amount added is referred to Table 2. A uniform and stable latex was obtained. After testing, the CRA peel force of the impregnated cord was 115.71N, and the amount of adhesive on the peel surface was judged to be Grade A.

[0140] Example 18

[0141] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that sodium hydroxide was used instead of ammonia in this embodiment. The specific amount added is referred to Table 2. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 103.64N after testing, and the amount of adhesive on the peel surface was judged to be Grade A.

[0142] Example 19

[0143] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that compound D was used to replace compound A in this embodiment. The specific amount added is referred to Table 2. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 112.78 N after testing, and the amount of adhesive on the peel surface was judged to be Grade A.

[0144] Example 20

[0145] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 9. The difference from Example 9 is that in this embodiment, compound D was used to replace compound A. The specific amount added is shown in Table 2. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 105.84 N, and the amount of adhesive on the peel surface was judged to be Grade A.

[0146] Example 21

[0147] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 10. The difference from Example 10 is that compound D was used to replace compound A in this embodiment. The specific amount added is referred to Table 2. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 91.09 N after testing, and the amount of adhesive on the peel surface was judged to be grade B.

[0148] Example 22

[0149] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 11. The difference from Example 11 is that in this embodiment, compound D was used to replace compound A. The specific amount added is shown in Table 3. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 99.47 N, and the amount of adhesive on the peel surface was judged to be grade B.

[0150] Example 23

[0151] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 12. The difference from Example 12 is that compound D was used to replace compound A in this embodiment. The specific amount added is referred to Table 3. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 108.96 N after testing, and the amount of adhesive on the peel surface was judged to be Grade A.

[0152] Example 24

[0153] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that compound E was used to replace compound A in this embodiment. The specific amount added is referred to Table 3. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 120.65N after testing, and the amount of adhesive on the peel surface was judged to be Grade A.

[0154] Example 25

[0155] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that compound F was used to replace compound A in this embodiment. The specific amount added is referred to Table 3. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 107.36 N after testing, and the amount of adhesive on the peel surface was judged to be Grade A.

[0156] Example 26

[0157] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 8. The difference from Example 8 is that compound G was used to replace compound A in this embodiment. The specific amount added is referred to Table 3. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 105.31 N after testing, and the amount of adhesive on the peel surface was judged to be Grade A.

[0158] Example 27

[0159] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 15. The difference from Example 15 is that compound D was used to replace compound A in this embodiment. The specific amount added is referred to Table 3. A uniform and stable latex was obtained. After testing, the CRA peel force of the impregnated cord was 99.72N, and the amount of adhesive on the peel surface was judged to be Grade A.

[0160] Example 28

[0161] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 16. The difference from Example 16 is that compound D was used to replace compound A in this embodiment. The specific amount added is referred to Table 3. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 96.29 N after testing, and the amount of adhesive on the peel surface was judged to be grade B.

[0162] Example 29

[0163] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 17. The difference from Example 17 is that compound D was used to replace compound A in this embodiment. The specific amount added is referred to Table 4. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 92.73 N after testing, and the amount of adhesive on the peel surface was judged to be grade B.

[0164] Example 30

[0165] In this embodiment, the impregnation solution was prepared and the impregnation test was completed according to the method of Example 18. The difference from Example 18 is that compound D was used to replace compound A in this embodiment. The specific amount added is referred to Table 4. A uniform and stable latex was obtained. The CRA peel force of the impregnated cord was 91.01 N after testing, and the amount of adhesive on the peel surface was judged to be grade B.

[0166] Comparative Example 1

[0167] This comparative example serves as a control over Examples 8, 11 to 14, 19, and 22 to 26 described above. The impregnation solution was prepared according to the method of Example 8, and the impregnation test was performed. The difference between this comparative example and the control examples is that water was used instead of the sulfur-containing active compound; that is, no sulfur-containing active compound was added. The specific amount added is shown in Table 5. This comparative example yielded a uniform and stable latex. The CRA peel strength of the impregnated cord was tested to be 61.98 N, and the amount of adhesive residue on the peel surface was determined to be Grade C.

[0168] Comparative Example 2

[0169] This comparative example serves as a control over Examples 9 and 20 described above. The impregnation solution was prepared according to the method of Example 8, and the impregnation test was performed. The difference between this comparative example and the control examples is that water was used instead of the sulfur-containing active compound; that is, no sulfur-containing active compound was added. The specific amount added is shown in Table 5. This comparative example yielded a uniform and stable latex. The CRA peel strength of the impregnated cord was tested to be 82.05 N, and the amount of adhesive residue on the peel surface was determined to be Grade B.

[0170] Comparative Example 3

[0171] This comparative example serves as a control over Examples 10 and 21 described above. The impregnation solution was prepared according to the method of Example 8, and the impregnation test was performed. The difference between this comparative example and the control examples is that water was used instead of the sulfur-containing active compound; that is, no sulfur-containing active compound was added. The specific amount added is shown in Table 5. This comparative example yielded a uniform and stable latex. The CRA peel strength of the impregnated cord was tested to be 42.26 N, and the amount of adhesive residue on the peel surface was determined to be Grade D.

[0172] Comparative Example 4

[0173] This comparative example serves as a control over Examples 15 and 27 described above. The impregnation solution was prepared according to the method in Example 8, and the impregnation test was performed. The difference between this comparative example and the control examples is that water was used instead of the sulfur-containing active compound; that is, no sulfur-containing active compound was added. The specific amount added is shown in Table 5. This comparative example yielded a uniform and stable latex. The CRA peel strength of the impregnated cord was tested to be 66.7 N, and the amount of adhesive residue on the peel surface was determined to be grade C.

[0174] Comparative Example 5

[0175] This comparative example serves as a control over Examples 16 and 28 described above. The impregnation solution was prepared according to the method of Example 8, and the impregnation test was performed. The difference between this comparative example and the control examples is that water was used instead of the sulfur-containing active compound; that is, no sulfur-containing active compound was added. The specific amount added is shown in Table 5. This comparative example yielded a uniform and stable latex. The CRA peel strength of the impregnated cord was tested to be 72.15 N, and the amount of adhesive residue on the peel surface was determined to be Grade C.

[0176] Comparative Example 6

[0177] This comparative example serves as a control over Examples 17 and 29 described above. The impregnation solution was prepared according to the method in Example 8, and the impregnation test was performed. The difference between this comparative example and the control examples is that water was used instead of the sulfur-containing active compound; that is, no sulfur-containing active compound was added. The specific amount added is shown in Table 5. This comparative example yielded a uniform and stable latex. The CRA peel strength of the impregnated cord was tested to be 59.37 N, and the amount of adhesive residue on the peel surface was determined to be Grade D.

[0178] Comparative Example 7

[0179] This comparative example serves as a control over Examples 18 and 30 described above. The impregnation solution was prepared according to the method of Example 8, and the impregnation test was performed. The difference between this comparative example and the control examples is that water was used instead of the sulfur-containing active compound; that is, no sulfur-containing active compound was added. The specific amount added is shown in Table 5. This comparative example yielded a uniform and stable latex. The CRA peel strength of the impregnated cord was tested to be 55.02 N, and the amount of adhesive residue on the peel surface was determined to be Grade C.

[0180] Comparative Example 8

[0181] This comparative example serves as a control over Examples 19 to 30 described above. The impregnation solution was prepared according to the method of Example 8, and the impregnation test was completed. The difference between this comparative example and the control examples is that the sulfur-containing active compound was replaced with JH-S69 coupling agent in this example. The water dispersion effect was compared; the specific addition amount is shown in Table 5. In this comparative example, stratification occurred during latex formation, making stable impregnation and testing impossible.

[0182] Table 1. Summary of data from Examples 8 to 14

[0183]

[0184]

[0185] Table 2 Summary of data from Examples 15 to 21

[0186]

[0187]

[0188]

[0189] Table 3 Summary of data from Examples 22 to 28

[0190]

[0191]

[0192] Table 4 Summary of data from Examples 29 and 30

[0193]

[0194]

[0195] Table 5 Summary of data from Comparative Examples 1 to 8

[0196]

[0197]

[0198] The above embodiments achieved good results in the one-bath impregnation process. Tests have shown that this application can also achieve the same results in the second impregnation process of the two-bath impregnation process.

[0199] The above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit it. The preferred embodiments have been described in detail. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the spirit and scope of the technical solutions of this application, and all such modifications and substitutions should be covered within the scope of the claims of this application.

Claims

1. A resin impregnation solution for a fiber skeleton material, characterized in that, include: A one-bath impregnation solution suitable for one-bath impregnation or a second impregnation solution suitable for two-bath impregnation; The solid content of the one-bath impregnation solution is 10% to 45%, and its dry weight includes: 15% to 70% phenolic adhesive resin, 20% to 70% latex and 3% to 20% sulfur-containing active compounds. The second impregnation solution has a solid content of 10% to 45%, and its dry weight includes: 10% to 60% phenolic adhesive resin, 30% to 90% latex and 3% to 20% sulfur-containing active compounds. The sulfur-containing active compound includes: a first compound and / or a second compound; The general structural formula of the first compound is as follows: , In the above formula, m is a positive integer, and the sum of n and k is greater than or equal to 1; The general structural formula of the second compound is as follows: , In the above formula, X is -R1-Si(R2). b (OR3) a The sum of a and b is 3, and c is a positive integer from 1 to 3; R, R', and R1 each include: unsubstituted or branched C1~C1. 10 Alkyl chain, or unsubstituted or branched heterochain, said heterochain being a carbon chain containing oxygen atoms, or unsubstituted or branched benzene; The branched chain includes: alkyl chain; R2 and R3 each comprise: C1~C2 alkyl groups, and R2 or R3 has R4 substitution; The R4 group includes a hydroxyl group or a carboxyl group.

2. The impregnation solution for the fiber skeleton material according to claim 1, characterized in that, The solid content of the one-bath impregnation solution is 15% to 35%, and its dry weight includes: 30% to 70% phenolic adhesive resin, 20% to 60% latex and 5% to 15% sulfur-containing active compounds.

3. The impregnation solution for the fiber skeleton material according to claim 1, characterized in that, The second impregnation solution has a solid content of 15% to 35%, and its dry weight includes 20% to 50% phenolic adhesive resin, 50% to 80% latex and 5% to 15% sulfur-containing active compounds.

4. The impregnation solution for the fiber skeleton material according to any one of claims 1 to 3, characterized in that, The one-bath impregnation solution and / or the second impregnation solution further include: an auxiliary agent with a total proportion of less than or equal to 10%; The additives include: pH adjusters, surfactants, film-forming agents, antioxidants, and / or crosslinking catalysts.

5. The impregnation solution for the fiber skeleton material according to any one of claims 1 to 3, characterized in that, The benzene has substituents, including hydroxyl or carboxyl groups.

6. The impregnation solution for the fiber skeleton material according to any one of claims 1 to 3, characterized in that, The latexes include: styrene-butadiene latex, styrene-butadiene-pyridine latex, butyl pyridine latex, vinyl pyridine latex, nitrile latex, hydrogenated nitrile latex, polybutadiene latex, chloroprene latex, and / or natural latex.

7. The impregnation solution for the fiber skeleton material according to claim 6, characterized in that, The styrene-butadiene rubber latex includes: styrene-butadiene rubber latex end-capped with carboxyl, hydroxyl, or anhydride, or styrene-butadiene rubber latex grafted with carboxyl, hydroxyl, or anhydride; the styrene-butadiene pyridine rubber latex includes: styrene-butadiene pyridine rubber latex end-capped with carboxyl, hydroxyl, or anhydride, or styrene-butadiene pyridine rubber latex grafted with carboxyl, hydroxyl, or anhydride; the styrene-butadiene pyridine rubber latex includes: styrene-butadiene pyridine rubber latex end-capped with carboxyl, hydroxyl, or anhydride, or styrene-butadiene pyridine rubber latex grafted with carboxyl, hydroxyl, or anhydride; the vinylpyridine rubber latex includes: vinylpyridine rubber latex end-capped with carboxyl, hydroxyl, or anhydride, or vinylpyridine rubber latex grafted with carboxyl, hydroxyl, or anhydride; the nitrile rubber latex includes: nitrile rubber latex end-capped with carboxyl, hydroxyl, or anhydride. The following are types of latex: latex, or nitrile butadiene latex grafted with carboxyl, hydroxyl, and anhydride groups; the hydrogenated nitrile butadiene latex includes: hydrogenated nitrile butadiene latex end-capped with carboxyl, hydroxyl, and anhydride groups, or hydrogenated nitrile butadiene latex grafted with carboxyl, hydroxyl, and anhydride groups; the polybutadiene latex includes: polybutadiene latex end-capped with carboxyl, hydroxyl, and anhydride groups, or polybutadiene latex grafted with carboxyl, hydroxyl, and anhydride groups; the chloroprene latex includes: chloroprene latex end-capped with carboxyl, hydroxyl, and anhydride groups, or chloroprene latex grafted with carboxyl, hydroxyl, and anhydride groups; the natural latex includes: natural latex end-capped with carboxyl, hydroxyl, and anhydride groups, or natural latex grafted with carboxyl, hydroxyl, and anhydride groups.

8. The impregnation solution for the fiber skeleton material according to any one of claims 1 to 3, characterized in that, The phenolic adhesive resin is formed by the condensation polymerization of phenolic monomers and aldehyde monomers; The phenolic monomers include: resorcinol, phloroglucinol, phenol, chlorophenol, aminophenol, or alkylphenol; The aldehyde monomers include: formaldehyde, alkyl aldehydes, benzaldehyde, benzoxaldehyde, or furfural.

Citation Information

Patent Citations

  • Improved cord-to-rubber bonding adhesive and method

    GB844795A